2016
DOI: 10.7748/en.2016.11577
|View full text |Cite
|
Sign up to set email alerts
|

Medication errors in intensive care units: nurses’ training needs

Abstract: Pharmacological knowledge is a prerequisite for the proper administration of drugs and for the clinical evaluation of the effects on the patient. This knowledge implies the understanding of the theoretical and clinical principles of pharmacology, the ability to contextualise medication management according to the complex and changing needs of patients, and it also includes the appropriate skills of drug administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 0 publications
1
16
0
5
Order By: Relevance
“…Environmental factors include noises, interruptions, and disorder. 29 Drug preparation in the adult ICU was performed on a dedicated bedside table on the ward, while the preparation in the NICU/PICU was performed in a separate room with an LAF. Both settings were affected by interruptions and the lack of preparation space.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors include noises, interruptions, and disorder. 29 Drug preparation in the adult ICU was performed on a dedicated bedside table on the ward, while the preparation in the NICU/PICU was performed in a separate room with an LAF. Both settings were affected by interruptions and the lack of preparation space.…”
Section: Discussionmentioning
confidence: 99%
“…Yet this strategy is perceived as suitable with regard to patient safety and is also recommended by the AHRQ (AHRQ, 2018). The importance of this aspect was also shown in a survey by Di Simone et al (2016). Respondents perceived training of new colleagues as a high-risk area.…”
Section: Discussionmentioning
confidence: 84%
“…Di Simone et al (2016) reported elements of nurses' knowledge, training, behavior and attitude potentially preventing medication errors in ICUs during administration of intravenous drugs. They concluded that the prerequisite for proper administration of drugs and evaluation of their effects is pharmacological knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…Other strategies have demonstrated to prevent ME based on implementing tools for guiding medication use and encouraging patient care by a multidisciplinary team. (Berdot et al, 2016;De Araújo et al, 2019;Di Simone et al, 2016).…”
Section: Discussionmentioning
confidence: 99%